Antifungal Efficacy during Candida krusei Infection in Non-Conventional Models Correlates with the Yeast In Vitro Susceptibility Profile - Scorzoni, Liliana [UNESP]; de Lucas, Maria Pilar; Mesa-Arango, Ana Cecilia; Fusco-Almeida, Ana Marisa [UNESP]; Lozano, Encarnación; Cuenca-Estrella, Manuel; Mendes-Giannini, Maria José Soares [UNESP]; Zaragoza, Oscar (Public Library of Science (PLoS), 2013)
The incidence of opportunistic fungal infections has increased in recent decades due to the growing proportion of immunocompromised patients in our society. Candida krusei has been described as a causative agent of disseminated fungal infections in susceptible patients. Although its prevalence remains low among yeast infections (2-5%), its intrinsic resistance to fluconazole makes this yeast important from epidemiologic aspects. Non mammalian organisms are feasible models to study fungal virulence and drug efficacy. In this work we have used the lepidopteran Galleria mellonella and the nematode Caenorhabditis elegans as models to assess antifungal efficacy during infection by C. krusei. This yeast killed G. mellonella at 25, 30 and 37°C and reduced haemocytic density. Infected larvae melanized in a dose-dependent manner. Fluconazole did not protect against C. krusei infection, in contrast to amphotericin B, voriconazole or caspofungin. However, the doses of these antifungals required to obtain larvae protection were always higher during C. krusei infection than during C. albicans infection. Similar results were found in the model host C. elegans. Our work demonstrates that non mammalian models are useful tools to investigate in vivo antifungal efficacy and virulence of C. krusei. © 2013 Scorzoni et al.
Keywords: amphotericin B; caspofungin; fluconazole; voriconazole; animal tissue; antifungal activity; antifungal susceptibility; arthropod larva; Caenorhabditis elegans; Candida krusei; candidiasis; concentration response; controlled study; cytolysis; drug efficacy; fungal virulence; Galleria mellonella; histopathology; in vitro study; minimum inhibitory concentration; nonhuman; phagocytosis; protection